PENGARUH ADMINISTRASI KEARSIPAN DAN PROFESIONALISME PEGAWAI TERHADAP KUALITAS PELAYANAN SUBAGIAN ADMINISTRASI PENDIDIKAN SEKOLAH TINGGI PENERBNAGAN INDONESIA CURUG TANGERANG - Dini Wagini (Politeknik Penerbangan Indonesia Curug, 2019)
Good service quality is a multidimensional assessment given to a service provider organization. To achieve optimal service quality need to be supported by some of the factors that influence it. This research was conducted in order to determine how much influence the archival and professionalism of employees to service quality subpart Administration Indonesia Civil Aviation Institute. The method used in this research is quantitative method, using statistics to help analyze the data obtained from the field. The main data was obtained by spreading questionnaires to a sample of 50 respondents, then processed using a correlation formula, determination and F test (Anova). The results showed that administration of archieves and competence of the employees have a strong correlation, evident from the calculation of 0.738. This shows the positive and significant correlation, then the coefficient of determination obtained for 54.5%while the remaining 45.5% influenced by other factors.